The Genetic Causes of Male Infertility in Iranian Population; A systematic Review - Azizi, Faezeh; Omrani, Mir Davood; Sadighi Gilani, Mohammad Ali; Hosseini, Jalil (Archives of Men’s Health, 2018)
Introduction: Infertility affects an estimated 15% of couples globally and in Iran, a quarter of couples experiences primary infertility. Males are found to be individually responsible for 20-30% of infertility cases and contribute to 50% of cases totally. When assisted reproductive technologies (ARTs) are used to acquire pregnancy, a sufficient (epi) genetic diagnosis of male infertility (MI) is of main matter to consider if a genetic abnormality will be transmit-ted to offspring. Infertility centers together with Infertility research centers had been founded since 1994 in Iran and many articles from research projects have been published. Materials and Methods: This literature investigated the possible genetic causes mechanisms underlying Iranian male infertility by extensive article searches. First, we reviewed available data from the Google Scholar, PubMed, Scopus, Web of Science, IranMedex, MEDLIB, IranDoc and Scientific Information Database were searched for articles published until 2018, using the MeSH terms for a variety of chromosome abnormalities, Y-chromosome microdeletions, gene mutations, expression and polymorphisms, Male infertility and/or Iranian, regional and international population, to provides the evidence- based and a comprehensive, up-to- date evaluation of the multifactorial factors involved in Iranian infertile men. Results: According to the strategy adopted initially, 274 manuscripts were found. After reviewing the titles, abstracts and manuscripts entirely cited, the total of 139 articles were obtained and selected according to the eligibility criteria. The 139 studies were divided into four predetermined categories that mentioned above. Studies have good methodological validity. The sample is quite heterogeneous, given the very different design of the studies. Conclusion: MI is a complex, multi-factorial disease and the underlying reasons frequently remain unknown. It seems that the first line of genetic diagnosis in Iranian male infertility is similar to Global One. In all investigations conducted in Iran, there are vacancies in studies such as epigenetic modification studies, RNA (lncRNA, miRNA and piRNA) abnormalities, mutation detection and polymorphism studies in other genes involved in the spermatogenesis process. At present, we have a little information for some polymorphisms (MTHFR, GST, ER, and DAZL) and mutations (mtDNA, CATSPER) which require more extensive studies. Such articles help to find a better insight into the causes of infertility in the Iranian men’s community and will provide valuable visions into the development of targeted personalized treatments for patients and the ascertainment of the reasons of idiopathic infertility.